Quantum Policy Gradient Algorithm with Optimized Action Decoding - Meyer, Nico; Scherer, Daniel D.; Plinge, Axel; Mutschler, Christopher; Hartmann, Michael (Proceedings of Machine Learning Research, 2023)
Quantum machine learning implemented by variational quantum circuits (VQCs) is considered a promising concept for the noisy intermediate-scale quantum computing era. Focusing on applications in quantum reinforcement learning, we propose an action decoding procedure for a quantum policy gradient approach. We introduce a quality measure that enables us to optimize the classical post-processing required for action selection, inspired by local and global quantum measurements. The resulting algorithm demonstrates a significant performance improvement in several benchmark environments. With this technique, we successfully execute a full training routine on a 5-qubit hardware device. Our method introduces only negligible classical overhead and has the potential to improve VQC-based algorithms beyond the field of quantum reinforcement learning.
CRIS-Team Scopus Importer:2023-10-27